MANAJEMEN STRATEGIK SEBAGAI PENDEKATAN DALAM MENGEMBANGKAN E-GOVERNMENT DI INDONESIA - S l a m e t, S l a m e t (IQTISHODUNA, 2013)
In this information age, quick, precise and accurate dissemination and access information is absolutely necessary. Similarly, information is one of the organization's resources that have to be managed as well as other organizational resources. To facilitate the dissemination and access of expected information, information and communication technology (ICT) or commonly known as ICT (Information Communication Technology) has a dominant role in terms of process, storage, retrieval, and dissemination of information. The involvement of integrated ICT in government agencies with the goal of providing ease process of service to citizens is called e-government. E-government has advantages and enormous significance for all citizens. However, to realize the target of e-government requires a substantial investment, on the other hand, the implementation of ICT is often facing a failure or lack of a strategic benefit. Therefore, to avoid the failure of ICT implementation to realize the target of e-government and pay attention to the amount of investment or budget, it is essential to manage the ICT department as the manager of e-government using strategic management as an approach. In here KPDE has a role as Chief Information Officer (CIO), which has the task of planning, implementer, coordinator, control and oversight of e-government implementation.